2023
DOI: 10.1002/cmtd.202200076
|View full text |Cite
|
Sign up to set email alerts
|

A Bright Surprise: Live‐Cell Labeling with Negatively Charged Fluorescent Probes based on Disulfonated Rhodamines and HaloTag

Abstract: Disulfonated rhodamines are photostable and bright dyes widely used in life science and optical microscopy. However, di‐sulfonated dyes were considered cell impermeable and not applicable in living cells. We challenged this assumption with 5 most popular rhodamines (Rho) having two carboxylic acid residues, versatile sulfonation patterns and emitting green (AS488), yellow (Rho530), orange (Rho565) and red (Rho590 and STAR RED) light. The probes comprising one rhodamine entity and a HaloTagTM amine (O2) ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…We first focused on the novel carborhodamine 59 (Scheme ), which is a fluorine-containing analog of ATTO 647N ( 105 ; Figure a). The “famous” ATTO 647N is perhaps the best dye for in vitro single-molecule imaging and has found widespread use as a label for advanced imaging experiments. ,, ATTO 647N conjugates have not been used in live-cell imaging experiments, however, due to structural constraints. A key design principle used in many ATTO dyes involves amidation of the ortho -carboxyl group on the pendant ring with 4-(methylamino)­butanoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…We first focused on the novel carborhodamine 59 (Scheme ), which is a fluorine-containing analog of ATTO 647N ( 105 ; Figure a). The “famous” ATTO 647N is perhaps the best dye for in vitro single-molecule imaging and has found widespread use as a label for advanced imaging experiments. ,, ATTO 647N conjugates have not been used in live-cell imaging experiments, however, due to structural constraints. A key design principle used in many ATTO dyes involves amidation of the ortho -carboxyl group on the pendant ring with 4-(methylamino)­butanoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…[11,12] Of the various pairs of self-labeling protein tags and fluorescent dyes, the combination of the HaloTag protein and rhodamine dyes has been most widely utilized to date. [13][14][15][16][17][18][19] In particular, rhodamine dyes bearing a ortho-carboxy-substituted aryl group at the 9-position are in a dynamic equilibrium between a fluorescent zwitterionic form and a non-fluorescent neutral spirolactone form, the latter being able to readily permeate the lipid bilayer (Figure 1a). [20][21][22][23] Exploiting this equilibrium, Johnsson and co-workers have developed a series of HaloTag probes based on silicon-rhodamine (SiR) (Figure 1b, SiR-Halo).…”
Section: Introductionmentioning
confidence: 99%
“…Charged bioactive molecules are currently used to selectively address extracellular targets: to inhibit extracellularly exposed receptors, photouncage signaling lipids locally at the plasma membrane, or bioorthogonally label cell-surface proteins tags. This field is also still in early stages and would benefit from more systematic evaluations: e.g., Belov et al recently revealed that double sulfonation, which had been assumed to guarantee cell impermeability, actually does not reliably prevent cell entry for rhodamines . While these methods are elegant and are starting to engage properly with membrane permeability, there remains an unmet need for generalized approaches to simultaneously mask and impermeabilize molecules, such that only intracellular reactions in permeabilized cells activate them: ideally giving “impermeable, off → ON” fluorogenic probes or prodrugs.…”
Section: Introductionmentioning
confidence: 99%